Factors Affecting Corn Farming Production in Lasalepa Sub-District Muna District - Atika, Vebby Surya; Limi, Muhammad Aswar; Mukhtar, Mukhtar (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
The objective of this research was to analyze the factors that affect the corn production in Lasalepa Sub-District, Muna District. This research was conducted in January - March 2020 in Lasalepa Sub-District, Muna District where the majority of farmers were engaged in corn farming. The primary and secondary data were collected through interview and literature study. The data analysis in this research employed regression equation using Cobb-Douglas production function model and a storage test against the classical assumptions which included multicollinearity and heteroscedasticity tests. Based on the results of regression analysis in this research, it can be concluded that the factors that significantly affected farmers' production were land area (X1) and seed (X4). According to the results of the research, it is necessary to add and reduce the factors of corn farming production in order to obtain profitable and optimal farming results. Furthermore, the role of government is also needed in terms of providing input subsidies so that farmers can use more inputs to increase their production.